Epistemic modalities of Korean language in the discussion of "Moon Jae-In Jeongbu, Jipgap Japgi Seonggonghalkka?" (문재인 정부, 집값 잡기 성공할까?) - Luviani, Eva Aida; Herniwati, Herniwati; Samsudin, Didin (Journal of Korean Applied Linguistics, 2024)
Epistemic modality is expressed through various grammatical forms, adverbs, and certain phrases that indicate degrees of certainty, doubt, or speculation. This research aims to determine the various forms and meanings of epistemic modality used by the speakers. The method used in this research was a descriptive qualitative method. The data source was a discussion entitled “Moon Jae-in Jeongbu, Jipgap Japgi Seonggonghalkka?”. The data collection techniques used in this research were literature study, listening, and note taking. The research employed the analysis technique proposed by Miles and Huberman, namely Interactive Model. The analysis results showed that there were nine out of eleven forms of epistemic modality: {(N)}, {(V)}, {(N) (V)}, {(N) (AUX)}, {(N) (COP)}, {(N) (AUX-Sfx) (Vneg)}, {(-Sfx) (V)}, {(AUX)}, and {(-SfxThe {(N) (V)} appears the most. This form is fully productive because it has a semantic appropriateness. Furthermore, the analysis results demonstrated that there were three gradients in the meaning of epistemic modality used by the speakers: certainty, probability, and possibility. The probability appears the most. This means that participants in the discussion are quite confident of their speech. The research results indicate that the participants in the discussion employed various ways to express the certainty, probability, and possibility of their speech.